Senescence (ageing) @ 2011 - Anjana Nigam (Wolters Kluwer Medknow Publications, 2011)
Ageing, also called as senescence, is one of the most complex, intrinsic, biological processes of growing older and resulting into reduced functional ability of the organism. Telomerase, environment, low calorie diets, free radicals, etc., are all believed to affect this ageing process. A number of genetic components of ageing have been identified using model organisms. Genes, mainly the sirtuins, regulate the ageing speed by indirection and controlling organism resistance to damages by exogenous and endogenous stresses. In higher organisms, ageing is likely to be regulated, in part, through the insulin/insulin-like growth factor 1 pathway. Besides this, the induction of apoptosis in stem and progenitor cells, increased p53 activity, and autophagy is also thought to trigger premature organismal ageing. Ageing has also been shown to upregulate expression of inflammatory mediators in mouse adipose tissue. The understanding of pathophysiology of ageing over the past few years has posed tremendous challenges for the development of anti-ageing medicine for targeted therapy. Future research areas must include targeted role of systemic inflammatory markers such as C-reactive protein and interleukin 6 and other biochemical and genetic studies including gene signaling pathways, gene microarray analysis, gene modulation, gene therapy, and development of animal/human models for potential therapeutic measures and evaluations.